2017
DOI: 10.3847/1538-4357/834/2/185
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Population of Bright Infrared Sources in the Small Magellanic Cloud

Abstract: We used Spitzer's Infrared Spectrograph (IRS) to observe stars in the Small Magellanic Cloud (SMC) selected from the Midcourse Space Experiment (MSX) Point Source Catalog. We concentrate on the dust properties of oxygen-rich evolved stars, which show less alumina than Galactic stars. This difference may arise from the SMC's lower metallicity, but it could be a selection effect: the SMC sample includes more stars which are brighter and thus more massive. The distribution of SMC stars along the silicate sequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 92 publications
1
26
0
Order By: Relevance
“…Ruffle et al (2015) classify it as O-rich due to the presence of strong crystalline emission features at 23, 28, and 33 µm. Kraemer et al (2017; They refer to the object as MSX SMC 049.) confirmed its optical C-rich spectrum, noted its dual C/O chemistry in the mid-infrared, and suggested that it may be a post-AGB object.…”
Section: Considering the Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Ruffle et al (2015) classify it as O-rich due to the presence of strong crystalline emission features at 23, 28, and 33 µm. Kraemer et al (2017; They refer to the object as MSX SMC 049.) confirmed its optical C-rich spectrum, noted its dual C/O chemistry in the mid-infrared, and suggested that it may be a post-AGB object.…”
Section: Considering the Samplementioning
confidence: 99%
“…At least two published papers have already investigated which filter combinations look to be most useful for distinguishing and characterizing different classes of objects. Kraemer et al (2017) examined the sample of SMC objects observed by the IRS, using the spectra to confirm the classifications. They found that the 5.6, 7.7, and 21 µm filters best separated C-rich from O-rich stars, while the 5.6, 10, and 21 µm filters best separated young stellar objects (YSOs) from planetary nebulae (PNe).…”
Section: The Potential Of Jwstmentioning
confidence: 99%
“…Instead, two-thirds of the sample were found to be carbon stars, and no heavily obscured oxygen-rich stars were detected, with the remaining third composed of RSGs, post-AGB stars, YSOs, PN, and oxygen-rich stars without significant dust. Other recent searches have discovered a few candidate OH/IR stars, some of which have been observed in the IR (Jones et al 2015;Kraemer et al 2017), and some at radio frequency, but only a few deeply embedded evolved stars like those within the LMC or our galaxy, either carbon-or oxygen-rich, have been found in the SMC (van Loon, Marshall & Zijlstra 2005;van Loon et al 2008;Lagadec et al 2007). It is not a requirement for OH/IR stars to have a high self-extinction, but as the maser luminosity is dependent on the dust, the most luminous maser sources are expected to.…”
Section: Previous Searches For Oxygen-rich Dusty Stars In the Smcmentioning
confidence: 99%
“…After observing BMB-B75, Jones et al (2015) found that the far-IR emission detected by Herschel was due to a spatially coincident galaxy. The mid-IR IRS spectrum of the source shows red-shifted (z ∼ 0.16) emission peaks of Polycyclic Aromatic Hydrocarbons (PAHs) at 6.3 and 11.3 µm and Ne iii at 12.8 and 15.5 µm from the background galaxy (Lebouteiller et al 2011;Kraemer et al 2017), but the silicate emission detected from the source appears unaffected. This source has also been found to have 6 cm continuum (Wong et al 2012), emission likely emanating from the background galaxy.…”
Section: Atca Sourcesmentioning
confidence: 99%
“…Figure 2 shows the FWHM range of 29 NIRCAM and MIRI filters compared to the SEDs of two C and M stars with increasing MLR. Kraemer et al (2017) and Jones et al (2017) have already investigated which filter combinations appear to be the most useful for distinguishing and characterizing different classes of objects.…”
Section: The Potential Of Jwstmentioning
confidence: 99%